Contribution of the horizontal transmission of the entomopathogenic fungus Beauveria bassiana to the overall performance of a fungal powder formulation against Triatoma infestans - Forlani, Lucas (2011)
The aim of study was to investigate the effect of hydroxylpropylmethylcellulose (HPMC), arabic gum (AG), konjac glucomannan (KG) and apple pectin (AP) at 2% (w/w, potato–wheat flour basis) on the potato–wheat dough (the mass ratio was 1:1) rheological, fermentation and bread making properties. The tan d of potato–wheat dough was significantly increased upon addition of adding HPMC which was close to wheat dough (0.531). Moreover, dough height during fermentation process was significantly improved on addition of hydrocolloids, with the order of HPMC (23.1 mm)[AP (19.3 mm)[AG (18.6 mm)[ KG (13.6 mm). Protein bands of potato–wheat dough were pale in the presence of hydrocolloids, suggesting the formation of higher molecular weight aggregates formed between proteins–hydrocolloids or proteins–proteins after fermentation process. Furthermore, HPMC significantly increased specific volume (from 1.45 to 2.22 ml/g), and hydrocolloids restricted the retrogradation of starch in potato–wheat breads.